(untitled) (Third Sector Social Economic Review, 2018)
The main purpose of this study is to explain the concept of workplace incivility, which is an underestimated subject in Turkey but a popular one in the international literature and to develop a Turkish incivility scale. Workplace incivility does not intend to harm others but it harms workplace norms and puts a peaceful workplace environment into danger. For this reason, it is an important topic for the business world. In this study, Coworker Incivility Scale and Supervisor Incivility Scale were developed seperately because workplace incivility has two different sources, coworkers and supervisor.